The Effectiveness of Project Based Learning Ecosystems Dioramas with Jelajah Alam Sekitar Approach against Students' Critical Thinking Ability and Creativity - Kurniyanti, Ratih; Tri Martuti, Nana Kariada; Alimah, Siti (FMIPA UNNES, 2019)
The purpose of this study was to analyze the effectiveness of Project Based Learning ecosystems dioramas with Jelajah Alam Sekitar approach against students’ critical thinking ability and creativity, and to analyze the relationship between critical thinking ability and students' creativity in Project Based Learning ecosystems dioramas with Jelajah Alam Sekitar approach. This research method is pre-experimental design with pre-test and post-test one group design. The results showed that Project Based Learning ecosystems dioramas with Jelajah Alam Sekitar approach was effective against students' critical thinking ability and creativity. The average of critical thinking ability in post-test is 84.96 and average of creativity in post-test is 84.50. The completeness of classical learning shows